2015
DOI: 10.1016/j.mrfmmm.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytochemical intervention on dibenzo[a,l]pyrene-induced DNA adduct formation

Abstract: Dibenzo[a,l]pyrene (DBP) has been found to be the most potent carcinogen of the polycyclic aromatic hydrocarbons (PAHs). Primary sources for DBP in the environment are combustion of wood and coal burning, gasoline and diesel exhaust, and tires. Given the likelihood of environmental exposure to DBP and strong experimental evidence of its potency, it is likely to contribute to lung cancer development. Intervention with compounds of natural origin (“phytochemicals”) is considered an effective means to prevent can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Previous work from our laboratory against breast and lung cancer has shown that Anthos possess both chemopreventive and therapeutic effects due to their roles as anti-inflammatory, antioxidant agents and modulators of CYP1A1 and CYP1B1 (18). We demonstrated that intervention with the anthocyanidin, delphinidin favorably modulated the underlying mechanisms of potent PAHs (19). Furthermore, although work has been conducted to research the impact of anthocyanins on CRC (20,21), no data have been reported to study the impact of Anthos or ETBF bacteria on alterations in phase I and II enzyme expression.…”
Section: Introductionmentioning
confidence: 61%
“…Previous work from our laboratory against breast and lung cancer has shown that Anthos possess both chemopreventive and therapeutic effects due to their roles as anti-inflammatory, antioxidant agents and modulators of CYP1A1 and CYP1B1 (18). We demonstrated that intervention with the anthocyanidin, delphinidin favorably modulated the underlying mechanisms of potent PAHs (19). Furthermore, although work has been conducted to research the impact of anthocyanins on CRC (20,21), no data have been reported to study the impact of Anthos or ETBF bacteria on alterations in phase I and II enzyme expression.…”
Section: Introductionmentioning
confidence: 61%
“…The title compound is a derivative of the 1,2-dithiole-3-thione family, which has attracted much interest because of the important bioactive properties and potential applications (Li et al, 2016, Russell et al, 2015, (Wallace et al, 2007). Recrystallization of 3H-1,2benzodithiole-3-thione in toluene solution leads to a monoclinic polymorph in the space group C2/c (Boukebbous et al, 2016) whereas recrystallization in diethyl ether solution leads to a second polymorph in the monoclinic system, and space group P2 1 /n (the present work).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…A similar conclusion was drawn for polyphenols to intervene dibenzo[a,l]pyrene‐induced DNA adduct formation in a newly published paper (Russell et al . ). The inhibitory effects of EGCG against DNA adduct formation may explain why in a clinical trial that a diet rich of green tea polyphenols may reduce genotoxicity in the human urinary bladder of smokers (Talaska et al .…”
Section: Resultsmentioning
confidence: 97%